Gender representation in senior high school textbook: A critical discourse analysis - Sudjana, Muhammad Ridwan Shaleh; Herdiawan, Rama Dwika; Kustini, Titin (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study investigates gender representation in the Indonesian senior high school English textbook Pathway to English for Grade 12 (2017) using Fairclough’s (2010) Critical Discourse Analysis, Gender Representation Theory, and Multimodality Theory. The analysis of ten purposively selected samples shows a clear imbalance: male characters appear more often and are portrayed in active, authoritative roles, while female characters are less visible and frequently confined to passive or supportive positions. Although a few instances highlight women in empowered roles, these are marginal and overshadowed by dominant patriarchal narratives. The findings indicate that the textbook perpetuates traditional gender ideologies rather than challenging them, emphasizing the need for more gender-sensitive educational materials that provide equitable role models for learners. Keywords: Gender representation; critical discourse analysis; English textbook;